DEVELOPING FINE MOTOR CAPABILITIES IN CREATING GEOMETRY PATTERN USING CUCHING LARI DAN DEMO RIANG IN GROUP A - Mahmudah Istiqamah; Asniwati Asniwati; Hadisa Putri (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2022)
The problem in this research is the development of fine motor aspect in making geometric pattern in RA. Raudatul Ilmi Gambut, there are children who are not yet skilled in making geometric pattern, using the contextual teaching and learning model with demonstration method and giving assignment will overcome children who are less interested and enthusiastic about learning activity, especially in making geometric pattern. This study uses a qualitative approach with the type of classroom action research (CAR). The setting of this research is group A children in RA Raudatul Ilmi. There are 11 children consist of 6 boys and 5 girls. The data collection technique was observation with qualitative data analysis. The result showed that the teacher's activity gets very good criteria. The children activity gets very active category and the result of the development of the children fine motor skill obtained the Undeveloped (BB) category at the first meeting and experienced development at the third meeting with the developing category very good (BSB). The use of this research can be suggested as varied learning for eaelychildhood.